Affective temperament profile in ankylosing spondylitis patients using TEMPS-A - Yildirim, Tulay; Solmaz, Dilek; Emul, Murat; Akgol, Gurkan; Yalvac, Dilek; Ersoy, Yuksel (Society of Physical Therapy Science (Rigaku Ryoho Kagakugakkai), 2017)
[Purpose] This study aimed to compare the most common dominant affective temperaments in Ankylosing Spondylitis patients and investigate the relationship between the dominant affective temperaments and pain levels, disease activity, quality of life, current depression, and anxiety level in Ankylosing Spondylitis patients. [Subjects and Methods] Fifty-one patients diagnosed with axial spondiloartropathy and forty-two age- and gender-matched control subjects were included in this study. Disease duration, erythrocyte sedimentation rate, serum C-reactive protein, pain by the Visual Analog Scale, disease activity by the Bath Ankylosing Spondylitis Disease Activity Index, functional status by the Bath Ankylosing Spondylitis Functional Index; psychological status by the Beck Depression Inventory, Beck Anxiety Inventory and overall health assessment by the Ankylosing Spondylitis Quality of Life Scale were assessed in patients. The Turkish version of the Temperament Evaluation of Memphis, Pisa, Paris and San Diego Auto Questionnaire was used to determine the dominant affective temperament. [Results] There was no statistical difference in the distribution of temperament subtypes between patients with Ankylosing Spondylitis and the controls. Depressive, anxious, and cyclothymic temperament scores were higher in patients with high values on the Bath Ankylosing Spondylitis Functional Index and Visual Analog Scale. There was a correlation between anxious subtypes of affective temperament scores and the value of Ankylosing Spondylitis Quality of Life Scale. Correlation analysis also found depressive, cyclothymic, irritable, and anxious temperament and psychiatric symptoms to be significantly related. [Conclusion] Affective temperament may contribute to symptoms of depression and anxiety in patients with Ankylosing Spondylitis and may increase disease activity and may reduce their quality of life. © 2017 The Society of Physical Therapy Science.
Keywords: Affective temperament; Ankylosing spondylitis; Disease activity